Evaluating the Impact of Language Barriers on Pre-Hospital Emergency Treatment- A Cross-Sectional Study in Hamad Medical Corporation Ambulance Service - Houcine Kanoun (18507487) (2024)
Background In the State of Qatar, where the population comprises 89.13% non-Arabic speakers, efficient communication in healthcare is crucial. The Hamad Medical Corporation Ambulance Service (HMCAS) faces unique challenges due to the language diversity of its patients and despite having staff from many nationalities. This study explored HMCAS staff opinion about the impact of language barriers on delivering pre-hospital emergency care in Qatar. Methods A cross-sectional study was conducted using a researcher-developed survey between January and February 2023. Using Solvin’s formula, the minimum sample size required for this survey was 295 staff members out of 1115 patient-facing staff. The Aiken V Content Validity Coefficient (CVC) was employed to assess content validity, whilst reliability was assessed via Cronbach's Alpha coefficient. Descriptive statistical analysis was subsequently undertaken for data interpretation. Results 395 staff answered the survey. The study, with Cronbach alpha=0.88 and CVC=0,93, found that HMCAS staff spoke multiple languages but still faced occasional communication difficulties due to language barriers (Figures 1 and 2). While most responders found the information, they could gather from patients to be 'slightly sufficient,' the willingness to learn new languages was notably high. Most were 'somewhat comfortable' using a bystander as an interpreter and were generally satisfied with their ability to communicate with the patient's family. The majority believed that learning more languages could potentially be beneficial. Conclusion The study highlighted the importance of addressing language barriers in pre-hospital settings in Qatar. It suggests that, despite a multilingual workforce, communication gaps could still potentially affect patient care. The high willingness among staff to learn additional languages presents an opportunity for training interventions, particularly in the context of global events. Therefore, policy changes aimed at language training could be instrumental in improving healthcare outcomes in a linguistically diverse setting.